American national biography - Garraty, John Arthur, 1920-; Carnes, Mark C. (Mark Christopher), 1950-; American Council of Learned Societies (New York : Oxford University Press, 1999)
"With more than 17,450 biographies written by more than 6,100 distinguished scholars and writers, the 24 volumes of the American National Biography provide a comprehensive examination of the incredible diversity of the men and women who have in some way shaped the history and development of the United States. The 20 million words of the American National Biography contain not only new findings about and interpretations of the roles of major historical figures, but also include scholarship about people hitherto excluded from the traditional biographical reference sources. Though published in the waning years of the 20th century, the American National Biography is a reference work for all times."--"Outstanding Reference Sources: the 1999 Selection of New Titles", American Libraries, May 1999. Comp. by the Reference Sources Committee, RUSA, ALA.
v. 1. Aarons-Baird -- v. 2. Baker-Blatch -- v. 3. Blatchford-Burnet -- v. 4. Burnett-Clarke, Lewis -- v. 5. Clarke, Mary-DaCosta -- v. 6. Dafora-Dubuclet -- v. 7. Dubuque-Fishbein -- v. 8. Fishberg-Gihon -- v. 9. Gilbert-Hand -- v. 10. Handerson-Hofmann -- v. 11. Hofstadter-Jepson -- v. 12. Jeremiah-Kurtz -- v. 13. Kurtzman-Lovecraft -- v. 14. Lovejoy-McCurdy -- v. 15. McCutcheon-Moskowitz -- v. 16. Mosler-Parish -- v. 17. Park-Pushmataha -- v. 18. Putman-Roush -- v. 19. Rousseau-Simmons -- v. 20. Simms-Stratemeyer -- v. 21. Stratton-Tunney -- v. 22. Tunnicliff-Welk -- v. 23. Wellek-Wrenn -- v. 24. Wright-Zworykin.
"Conceived as the successor to the Dictionary of American biography, first published between 1926 and 1937"--Vol. 1, p. xvii.
"Published under the auspices of the American Council of Learned Societies."
Includes bibliographical references and index.
English.
Keywords: United States -- Biography -- Dictionaries